1970
DOI: 10.3329/bjb.v39i1.5531
|View full text |Cite
|
Sign up to set email alerts
|

Marine algae of St. Martin's Island, Bangladesh. VIII. new records of red algae (Rhodophyceae)

Abstract: Ceramium brevizonatum var. caraibica Peter. et Børg., Dasya corymbifera J. Ag., Dudresnaya hawaiiensis R.K.S. Lee, Chrysymenia agardhii Harv. and Hypnea boergesenii Tanaka are recorded and described for the first time from the St. Martin's Island, Cox's Bazar, Bangladesh. Key words: Seaweeds; Red algae; Dudresnaya hawaiiensis; St. Martin's Island; Bangladesh DOI: 10.3329/bjb.v39i1.5531Bangladesh J. Bot. 39(1): 87-96, 2010 (June)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1970
1970
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Lentil, field pea, soybean and faba bean produce aerenchyma within roots to facilitate the aeration of flooded tissue (Thomas et al 2005;Stoddard et al 2006;Solaiman et al 2007). Waterlogged plants of faba bean, soybean, and mungbean produce adventitious roots to enhance oxygen transport from the stem to the roots and to reduce flooding injury (Henshaw et al 2007;Solaiman et al 2007;Islam et al 2010). We monitored the root system only at maturity and did not observe adventitious roots in any of the crop.…”
Section: Root and Nodule Dry Weightmentioning
confidence: 99%
“…Lentil, field pea, soybean and faba bean produce aerenchyma within roots to facilitate the aeration of flooded tissue (Thomas et al 2005;Stoddard et al 2006;Solaiman et al 2007). Waterlogged plants of faba bean, soybean, and mungbean produce adventitious roots to enhance oxygen transport from the stem to the roots and to reduce flooding injury (Henshaw et al 2007;Solaiman et al 2007;Islam et al 2010). We monitored the root system only at maturity and did not observe adventitious roots in any of the crop.…”
Section: Root and Nodule Dry Weightmentioning
confidence: 99%
“…by Islam et al (2010) have been reported. Habitat and local distribution: Plants were growing on Liagora harveyana Zeh along with Polysiphonia harveyi Bailey in St. Martin's Island (Islam et al 2010); collection no. 252; 6 January, 1986; a few.…”
Section: Resultsmentioning
confidence: 96%
“…Unfortunately, seaweed is almost unknown to Bangladeshi people as a source of food and has only been utilised by Mog or Rakhyine ethnic communities. In Bangladesh, naturally growing seaweeds are seen in the littoral and sub-littoral zones of St. Martin's Island to the Sundarbans Mangrove forest and are available from October to April throughout the whole southern coast (Islam and Aziz 1987;Islam 1998). Water quality parameters and rocky substratum makes St. Martin's Island an excellent place for naturally occurring seaweeds (Khan 1990;Tomascik 1997;Zafar 2004a).…”
Section: Grey Mullet (Mugil Cephalus)mentioning
confidence: 99%